Sosialisasi Pembuatan Kerajinan Bingkai Foto Untuk Menumbuhkan Kreativitas Berwirausaha Pada Anak-anak Di SDN 24 Kota Bengkulu - Ardiana, Rina; Anggriani, Ida; Damarsiwi, Eska Prima Monique; Effendi, Yanto (Jurnal Gotong Royong, 2024)
The aim of this Community Service Activity is to increase the creativity of children at SD Negeri 24 Bengkulu City by socializing the making of handicrafts from rice paper to foster entrepreneurial creativity. The material provided is about the positive activity of making handicrafts from rice paper so that it can open up insight that handicrafts can also be used as a business opportunity from an early age. The technique and method for implementing Community Service activities used is socialization. Techniques for implementing Community Service activities used by 25 students at SDN 24 Bengkulu City. This Community Service activity is in the form of a scientific article published in the Dehasen Scientific Journal for the Nation. It is hoped that this activity will be useful and increase knowledge and understanding for children at SDN 24 Bengkulu City.